Physicochemical and structural properties of major protein fractions of two varieties of nea-cowpea (vigna unguiculata l.): a comparative study - Avanza, María Victoria (2015)
Fil: Avanza, María Victoria. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.